Pengaruh Stres Kerja dan Motivasi Terhadap Kinerja Karyawan - Zulkifli, Irwan (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
This study aims to evaluate the impact of work stress and motivation on employee performance at PT. X. Data was collected from 44 respondents out of the total population of employees in the company through a questionnaire method. Quantitative data analysis was conducted using various techniques, including instrument testing, classic assumption testing, multiple linear regression analysis, and hypothesis testing. The results of the study indicate that work stress has an influence on employee performance, while work motivation has a positive impact. Simultaneously, both independent variables (work stress and work motivation) affect the dependent variable (employee performance). The coefficient of determination indicates that 20.3% of the variation in employee performance can be explained by work stress and work motivation, while the remaining 79.7% is influenced by other factors not examined in this study.